Towards Feature-based Product Line Engineering of Technical Systems. (2016) - Koch, Thorsten; Holtmann, Jörg; Schubert, David; Lindemann, Timo
Abstract: The development of today's technical products (e.g., in automation) is characterized by high customer expectations regarding the product individualization, which causes a wide range of product variants. Original equipment manufacturers (OEMs) can apply classical approaches from product line engineering, like feature modeling, to cope with the variability and the induced develop- ment complexity. Our tool support for feature models integrates a variety of feature model extensions like feature attributes and properties, logical constraints between features and feature properties, and the distinction between features and feature realiza- tions. Beyond that, technical products have geometrical dimensions. The OEM specifies Computer Aided Design (CAD) models to consider these geometrical dimensions and to virtually layout particular product variants. Geometrical assembly constraints specify how parts of the product can be arranged in a CAD model. However, a potential product customer cannot configure an individual product variant and virtually layout this variant in the same software tool since the respective information stems from different sources. In order to cope with this problem, we present in this paper an extension of our tool support for feature models to specify geometrical assembly constraints. Based on the proposed extension, we outline our research roadmap to consider these constraints in an online shop of an e-commerce system, in which a potential customer shall be able to configure a product variant and to virtually layout it according to the assembly constraints.